Determining environmental limits of threatened species: the example of the wallum sedgefrog Litoria olongburensis. Issue 6 (30th June 2016) - Shuker, Jon D.; Simpkins, Clay A.; Hero, Jean‐Marc
Abstract: In an environment that is changing due to anthropogenic processes, managers responsible for conservation of threatened species need to know environmental limits beyond which those species are at risk of extinction. We demonstrate estimation of environmental limits for a threatened species using a novel combination of response modeling techniques. Our study species was Litoria olongburensis (wallum sedgefrog), which has a biphasic lifecycle (aquatic larvae and terrestrial adult phases) with larvae developing in naturally acidic wetlands of coastal sandy lowlands ("wallum") of subtropical eastern Australia. Land development in, and around, areas occupied by the frog is the main cause of the species' decline, while climate change is emerging as a new threat. The species will continue to decline where these processes destroy, fragment or degrade habitat. We surveyed waterbodies throughout the latitudinal range of the species' distribution, recording wallum sedgefrog density and environmental variables including abiotic waterbody characteristics, key vegetation types, potential competitors and potential predators. For each environmental variable, we tested the fit of increasingly complex response models to the highest possible quantile of wallum sedgefrog density. The best‐fitting model indicated the most likely response, if any, to the variable. This model was then applied to estimate environmental limits. Our analysis indicated wallum sedgefrogs were less likely to occur in waterbodies with pH outside 3.53–4.61 (± 0.11) and maximum water depth outside 23.4–46.0 (± 3.5) cm, and their density decreased with increasing densities of eastern sedgefrogs, wallum froglets and common froglets. The optimal pH levels and water depths indicated by our analysis provide a necessary baseline for predicting and responding to impacts on wallum sedgefrogs caused by changes in land use or climate. The negative relationship with eastern sedgefrogs supports the hypothesis that competition from eastern sedgefrogs is the mechanism that limits occurrence of wallum sedgefrogs in higher pH wetlands. The modeling framework that we developed for our study can be applied to improve management of other species exposed to anthropogenic threats including climate change.